2012
DOI: 10.1103/physrevb.86.174117
|View full text |Cite
|
Sign up to set email alerts
|

Antiferrodistortive phase transition in pseudorhombohedral (Pb0.94Sr0.06)(Zr0.550

Abstract: The controversies about the structure of the true ground state of pseudorhombohedral compositions of Pb(Zr x Ti 1-x )O 3 (PZT) are addressed using a 6% Sr 2+ substituted sample with x=0.550. Sound velocity measurements reveal a phase transition at T c~2 79K. The temperature dependence of FWHM of (h00) pc peaks and the unit cell volume also show anomalies around 279K even though there is no indication of any change of space group in the synchrotron X-ray powder diffraction (SXRD) patterns. The neutron powder di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…296,297 At x ≈ 0.52, PZT is characterized by the coexistence of tetragonal, rhombohedral, and a more recently identified intermediate monoclinic phase, [298][299][300][301][302][303] defining the so-called morphotropic phase boundary; such phase coexistence is responsible for the large piezoelectric response of PZT at this composition. 165,297,[304][305][306] In the context of interfacial ferroelectric devices, the tetragonal phase of PZT is the most interesting on account of the higher Curie temperature and a larger ferroelectric polarization along the tetragonal axis. 174,235,301,[307][308][309][310] The epitaxial growth of thin PZT films has been demonstrated on several substrates using various deposi- or on undoped SrTiO 3 with a conducting oxide buffer layer, which provide a good template for the growth of tetragonal PZT (x < 0.5).…”
Section: Batiomentioning
confidence: 99%
“…296,297 At x ≈ 0.52, PZT is characterized by the coexistence of tetragonal, rhombohedral, and a more recently identified intermediate monoclinic phase, [298][299][300][301][302][303] defining the so-called morphotropic phase boundary; such phase coexistence is responsible for the large piezoelectric response of PZT at this composition. 165,297,[304][305][306] In the context of interfacial ferroelectric devices, the tetragonal phase of PZT is the most interesting on account of the higher Curie temperature and a larger ferroelectric polarization along the tetragonal axis. 174,235,301,[307][308][309][310] The epitaxial growth of thin PZT films has been demonstrated on several substrates using various deposi- or on undoped SrTiO 3 with a conducting oxide buffer layer, which provide a good template for the growth of tetragonal PZT (x < 0.5).…”
Section: Batiomentioning
confidence: 99%
“…Besides, a number of reports have also been published in the recent years on the effect of dopants on the dielectric and electromechanical response of PZT ceramics. Solanki et al [12] have reported that PZT doped with 6 % Sr 2? shows the presence of Cc space group.…”
Section: Introductionmentioning
confidence: 99%
“…5(c) that the intensity of the (1/2 1/2 1/2) pc peak is too small to be observable above the background counts/fluctuations. In fact, the calculated intensity of this peak is only ~0.12% of the strongest (111) pc perovskite reflection, which is of the order of the background counts in our neutron diffraction data 24 . It is important to emphasize that the non observation of (1/2 1/2 1/2) pc superlattice peak in the neutron diffraction pattern is as enigmatic as the non observation of (3/2 1/2 1/2) pc , (3/2 3/2 1/2) pc and (5/2 1/2 1/2) pc superlattice reflections in the SXRD patterns, as the SXRD intensities of these peaks is comparable to the neutron intensity of the (1/2 1/2 1/2) pc peak.…”
mentioning
confidence: 99%
“…However, the non-observation of the weak (1/2 1/2 1/2) pc superlattice peak in the neutron powder diffraction patterns is as enigmatic as the non-observation of the rather intense neutron (3/2 1/2 1/2) pc, (3/2 3/2 1/2) pc and (5/2 1/2 1/2) pc superlattice peaks in the synchrotron X-ray powder diffraction patterns. Most likely, it is because the intensity of these reflections is too small 24 ( 0.1% of the most intense (110) pc peak) to be observable above the background counts for both the neutrons and the X-rays. In view of this, we recently 24, 25 adopted an alternative strategy for resolving the Cc versus R3c controversy for the ground state of PZT.…”
mentioning
confidence: 99%
See 1 more Smart Citation